Building sustainable capacity for policy research with impact: Lessons from PRCI in Asia - Babu, Suresh Chandra; Tschirley, David; Boughton, Duncan; Srivastava, Nandita (Michigan State University, 2024)
This policy brief summarizes results of an assessment of the impacts of assistance provided by the Feed the Future Innovation Lab for Food Security Policy Research, Capacity, and Influence (PRCI) to agricultural and food policy think tanks and research centers in six countries of Southeast Asia (Thailand, Cambodia, and Laos) and South Asia (India, Nepal, and Sri Lanka) from mid-2019 to mid- 2024. The brief’s objectives are to (1) distill the progress and accomplishments of the policy think tanks that PRCI supported and the related impacts that this assistance had on their organizations, and (2) draw lessons for the design of future programming that aims to support sustained enhancement of institutional capacity for applied food and agricultural policy research that has influence on policy processes and outcomes.